THE M/OTHER STORY IN TONI MORRISON’S BELOVED: THE TRAUMA OF MOTHERHOOD/MOTHERLAND AND THE AFRICAN AMERICAN IDENTITY - Hssairi, Rania Kerkeni (Sanata Dharma University, Yogyakarta, 2024)
Inspired by the story of Margaret Garner, Toni Morrison’s Beloved revolves around the story of Sethe, among those of other slave mothers, and her struggle to experience motherhood against the horrors and terrors of slavery and white exploitation. In light of Lacanian theory, this study deals with the traumatic nature of motherhood in the institution of slavery, while exploring the unconventional m(other) portrait drawn by Morrison in her novel. Connectedly, drawing on Stuart Hall’s insights about the issues of identity and belonging, this paper also investigates the role of the trauma resulting from lost motherhood in the loss of the African motherland and the molding of the African-American identity.